Public Ethos in the Pandemic Rhetorical Situation: Strategies for Building Trust in Authorities’ Risk Communication (Journal of International Crisis and Risk Communication Research, 2021)
As illustrated by the COVID-19 pandemic, risk and crisis communication are crucial responsibilities of modern governments. Existing research on risk and crisis communication points to the importance of trust, both as a resource in and an end goal of communicative activities. In this paper, we argue that revisiting the classical rhetorical concept of ethos in combination with the modern concept of the rhetorical situation can contribute to fitting responses in risk and crisis communication. The paper examines how appeals to ethos may build trust in health authorities’ public communication during the COVID-19 pandemic. Through interviews and participant observation in public health institutions that handle the COVID-19 pandemic in Norway, the paper finds that understanding the rhetorical situation of the pandemic allows for a better understanding of the available means of persuasion. For instance, through the active communication of transparency and independence when faced by uncertainty and rapidly changing information.